Female neophobia predicts the use of buildings as nesting sites in a Neotropical songbird - Batisteli, Augusto F.; Pizo, Marco A. [UNESP]; Sarmento, Hugo (Elsevier, 2022)
Neophobia (i.e. the degree of avoidance to novel situations) is a personality trait that may predict the ability to exploit new resources, which potentially affects the success of settlement of urban animal populations. Despite the increasing amount of information on birds using artificial structures as nesting supports, the hypothesis that the propensity to nest on buildings is related to parental personality has never been tested. In a field experiment, we addressed the relationship between female neophobia and the use of buildings as nesting sites in an urban population of the pale-breasted thrush, Turdus leucomelas, in southeast Brazil. We placed novel objects near active nests placed on buildings (N = 16) and trees (N = 12) and measured the latency of incubating females to resume incubation. Using linear mixed-effects models, we estimated the individual repeatability of this behavioural response and tested whether latency times differed between neophobia and control tests within nesting substrate types. We found significant repeatability for the latency to resume incubation during neophobia tests (r = 0.353), indicating that this behaviour was consistent at the individual level as expected for personality-mediated responses. Latency was higher in neophobia than in control tests, but only among females that nested on trees. Previous studies suggest that less neophobic individuals tend to express more exploratory and innovative behaviours, which may have enhanced the use of buildings as nesting sites by fearless females. We conclude that less neophobic females are more prone to nest on buildings in the pale-breasted thrush. Our study is the first to link bird neophobia and the use of buildings as nesting substrates, evidencing that the exploitation of artificial resources may be associated with the predominance of certain animal personalities in anthropic environments.
Keywords: anthropogenic resource; innovative behaviour; neophobia; nest placement; thrush; urban bird